Analisis Faktor–Faktor yang Mempengaruhi Kinerja Tukang pada Proyek Konstruksi - Wahyu Bumulo; Beby Sintia Dewi Banteng; Arfan Utiarahman (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Occupational Safety and Health is essential for construction work, but there are still some problems in implementing it. Among the challenges include lack of awareness and understanding of the importance of OHS, lack of adequate training for workers, and lack of supervision and enforcement of OHS-related regulations. Therefore, research and risk analysis of OHS in construction work is needed to find potential hazards, evaluate risks, and develop effective control solutions. This research is categorized as quantitative and also descriptive observational approach. This study also used a questionnaire based on the Hirarc method and conducted a risk analysis on the IAIN Sultan Amai Gorontalo Lecture Building Construction project. out of 50 respondents there were the same answers and repeated in each job. Thus, 12 types of risks were obtained with a total of 40 risk items identified. These risks are the most significant and recurring risks, therefore require special attention in risk planning and management. From the results it can be concluded that the stages of identifying risk management in the Upper structure work are identifying risks, risk assessment, and risk control.